ANALISIS PERLAKUAN AKUNTANSI AKTIVA TETAP PADA RSUD CURUP - Offiryadi (Politeknik Raflesia Press, 2020)
This research was conducted at Curup Hospital which is located at Jl. Basuki Rahmat No.10, Dwi Tunggal, Curup, Rejang Lebong Regency, Bengkulu Province. Curup Hospital is on Jl. Basuki Rahmat No.10, Dwi Tunggal, Curup, Rejang Lebong Regency, Bengkulu Province. The purpose of this research was to determine the depreciation of fixed assets using the straight-line method at Curup Hospital. The method used for this research was descriptive method, namely comparing the conditions actually happens with theories that are relevant to the related problem. Data collection techniques and other information were carried out by means of interviews and documentation. Based on the research conducted on the Curup Regional Hospital, several problems were found related to the depreciation of fixed assets: it was found that the staff did not understand the depreciation of fixed assets so that in some problems, namely elimination or discontinuation of fixed assets which are no longer used and the determination of the costs incurred for repairs of fixed assets are also ambiguous.